The Relation between Individual Characteristics and Job Stress in PT. PAL Indonesia - Siti Hardiyanti Putri Pratiwi; Tri Martiana; Shintia Yunita Arini (Universitas Airlangga, 2020)
Introduction: Quality Assurance and Quality Control Division workers are challenged by various mental and physical pressures that might trigger job stress. Many factors contribute to job stress, one of them is the individual factor. This study’s purpose was to examine and analyze whether or not there was a relation between the individual characteristic factors and job stress at PT. PAL Indonesia (Quality Assurance and Quality Control Division). Methods: This research was a cross-sectional study. This research had a population of 49 people. The sample was counted using a simple random sampling method and 44 people were obtained as samples. This study’s independent variables were individual characteristics (working period, age, sex, and marital status) and job stress as the dependent variable. Data collection methods for this study were interviews with a questionnaire guide. The data analysis technique used was Fisher's Exact. Results: The result of Fisher Exact statistical test showed that there was not any relation between working period and job stress (p = 0.170), age and job stress (p = 0.456), gender and job stress (p = 0.290), marital status and job stress (p = 1,000). Conclusion: It can be concluded that individual characteristics has no significant relationship with job stress on employees of the Quality Assurance and Quality Control division of PT. PAL Indonesia (Persero). Keywords: individual characteristics, job stress, quality assurance and quality control division